Evaluation Of Wound Healing Efficacy Of Hydrogel Containing Dalbergia Latifolia (Roxb) Bark Extract. - KR, Dhanush; Babu VL, Ashoka; Nayak A, Damodar (Journal of Neonatal Surgery, 2025)
Skin is vulnerable to a variety of injuries, necessitating effective wound healing solutions. The present study aims to evaluate wound healing properties of Dalbergia latifolia (Roxb) bark. Alcoholic extract was prepared and analysed by GC–MS and further subjected to molecular docking studies. The hydrogel was prepared with 5%, 7.5%, and 10% concentrations of Dalbergia latifolia (Roxb) bark extract and characterized by pH, viscosity, swelling index, drug content, in-vitro drug release and kinetic study. Wound healing potential of alcoholic extract was evaluated by incision and excision wound models following acute dermal irritation studies. Histopathological studies and haematological parameters were determined for excision model, tensile strength was performed for incision wound skin. Phytochemical screening showed the presence of flavonoids, phytosterols, phenolics, and tannins in alcoholic extract. GC-MS analysis revealed multiple phytoconstituents, Molecular docking studies performed with targets TGF-β, EGFR, GSK-3β, IL1, and FGFR1, 5QU0 revealed high binding affinities. ADMET studies showed better pharmacokinetic and drug likeliness property. Acute dermal irritation tests showed no significant irritation, while in vivo studies proved that 7.5 % hydrogel has potential wound healing efficacy. Histopathological examination confirmed enhanced fibroblast proliferation and collagen formation in treated wounds. In conclusion, hydrogels contain- D. latifolia extract demonstrated significant potential for wound healing, supported by both chemical analysis and biological evaluation..